(3cJGH GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO adhdG Cf GdYGOI ShZJ GdGUGZQ GdEfHSGW Edi GdCcGHQ s
(3BNQgG (B:s
(3HGaQGO Gdbhd ai Jdc GdeYGfi GSJfaOJ ai GdCFJeGQ ZGjI GdLgO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(3/150) s
Keywords: (3GdadSaI hGdefWbs